Determinan Return On Asset (ROA) Bank Pembiayaan Rakyat Syariah (BPRS) di Jawa Barat periode 2014-2016 - Ayuk Nur Cahyati (FAI, 2017)
Determinan Return On Asset (ROA) Bank Pembiayaan Rakyat Syariah (BPRS) di Jawa Barat periode 2014-2016